Колебательные свойства электрических систем - Литкенс Ирина Владимировна (Энергоатомиздат, 1988)
Экземпляры: КХ (20080804) / Инвентарный номер: 926953 / Цена: 0.75 / Сис.шифр: 31.27 / Авт.знак: Л 64 / ГРНТИ: 45 / ББК: 31.27